Efek Penerapan Teknologi Pertanian terhadap Kehidupan Sosial Ekonomi Masyarakat Mawasangka Timur - Halim, Halim (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2010)
The research purpose to analyze the effect of agriculture technology to social economic of Mawasangka Timur’s society. Agriculture of technology implementation in the economic sector and Mawasangka Timur’s economic growth and construct simulations of technology mastery effort on key sectors in the long run. The agriculture technology component to analyzes in this research is the application of herbicides to weed control, application insecticide to insect control, application of fertilizer to the soil and using of hands tractors to tillage. It is employed series dynamics Input-Output table analyzes, because of explicit information about agriculture technology implementation through Leontief Coefficient of Technology. The research result shows that’s agriculture technology implementation determine the growth of Mawasangka Timur’s economic society in a very small proportion and hight proportion is application of fertilizer to soil about 15% average and shows in fast-growing contribution. The agriculture technology effect for economic growth, in the long run, is fertilizer as 50,12%.